(untitled) (Bangladesh Journal of Botany, 2025)
This study was aimed to investigate the effects of salt stress and melatonin on the seed germination of leaf chicory. Salt stress significantly reduced various seed germination indexes, while melatonin treatment had a positive effect on seed germination. 250 µmol/l concentration of melatonin was identified as the optimal concentration for improving seed germination. Mixed treatment with melatonin significantly improved all seed germination indexes compared to separate salt stress. These findings suggest that melatonin alleviates the inhibitory effects of salt stress on seed germination and enhances the salt tolerance in leaf chicory. Bangladesh J. Bot. 54(2): 245-252, 2025 (June)